PENGARUH FORMULA SOSIS DENGAN PENAMBAHAN TEPUNG BIT (Beta vulgaris) PADA MUTU SOSIS DAGING BURUNG PUYUH AFKIR (Coturnix coturnix Japonica) - Nelis Oetavi A.; Khusnul Khotimah; Elfi Anis Saati (Universitas Muhammadiyah Malang, 2019)
Sausage is a popular food product consumed by the world's population. Meat quail (Coturnix coturnix) is a meat product which has good prospects for use as a raw material for making sausages. The superiority of quail meat is a high protein content between 16,78% - 20,40% and about 70-74% yield of the weight of quail life. In order to increase consumer’s acceptability, the sausage needs a quality improvement especially in terms of appearance (color). One of the ingredients which have the potential as a natural dye is a beetroot (Beta vulgaris). The beetroot has a content of 200 mg of betanin/100 g. This study aims to determine the effect of different sausage formulas and the concentration of beetroot flour toward physicochemical and sensory properties of quail meat sausage. The research method used Randomized Block Design (RBD) with variation of beetroot flour concentration (0%, 1%, 2%, 3%, 4%, and 5% w/w of quail meat). Parameters analyzed were moisture content, protein content, fat content, ash content, antioxidant activity, texture, brightness, redness, yellowish, aroma, taste, and appearance. The best treatment is the quail meat sausage with the addition of the concentration of beet flour by 5% with water content 63,52%, protein content 13,44%, fat content 3,80%, ash 2,81%, antioxidant activity 47,95%, texture 5,19 N/mm2, lightness 44,33, redness 25,47, yellowish 13,20, aroma 3,4 of 5,00, taste 3,5 of 5,00, and appearance 4,04 of 5,00. All treatments have been in accordance with the standards based on SNI No. 01-3820-1995.